Switching From Originator to Biosimilar Infliximab in Paediatric Inflammatory Bowel Disease Is Feasible and Uneventful. Issue 6 (December 2018) - Gervais, Lisa; McLean, Luke L.; Wilson, Michelle L.; Cameron, Carol; Curtis, Lee; Garrick, Vikki; Armstrong, Kat; Tayler, Rachel; Henderson, Paul; Hansen, Richard; Chalmers, Iain; Wilson, David C.; et al.
Abstract : ABSTRACT: The safety, clinical efficacy, and cost-effectiveness of biosimilar infliximab in adult inflammatory bowel disease (IBD) have now been extensively shown. Limited data have been collected in the paediatric setting. We report nationwide, prospective, clinical safety and effectiveness data for patients from all 3 Scottish paediatric inflammatory bowel disease networks switching from originator to biosimilar infliximab. Prospective clinical data were collected for 33 patients. Information was collected from electronic patient records, laboratory reports, and patient case notes. There were no clinically significant changes to disease activity, biomarkers, antidrug antibodies, or trough drug levels ( P  > 0.1) within a 12-month follow-up period; in addition, there were no significant adverse events reported. No infusion reactions were seen in the 264 infusions delivered. Switching from originator infliximab to the biosimilar (CT-P13) appears to be associated with neither an increase in infusion reactions nor significant loss of effectiveness in the short term.